2019
DOI: 10.14429/djlit.39.5.14303
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis of Research Output on the Internet of Things in the Arab World

Abstract: Arab countries understand the importance of the Internet of things for the development of society. This entails many efforts to conduct research related to the Internet of things in the Arab countries. Analysing contributions of researchers to the Internet of things research could be useful to go further in this filed. In this study, bibliometric techniques are used to investigate publications indexed in the Scopus database with the affiliation to the Arab countries. The paper used researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The regional environmental economy itself has complexity. From the perspective of semantic web services, the collaborative environmental economy and integration technology are analyzed [ 15 , 16 ].…”
Section: Related Workmentioning
confidence: 99%
“…The regional environmental economy itself has complexity. From the perspective of semantic web services, the collaborative environmental economy and integration technology are analyzed [ 15 , 16 ].…”
Section: Related Workmentioning
confidence: 99%
“…Kaba and Ramaiah (2019) used bibliometric techniques to highlight the productivity and impact of research on the internet of things (IoT) contributed by the Arab World. The researchers found better performance by the Arab World in IoT as compared to medical and environmental research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Only a few studies have reported an increase in the medical and health sciences publications contributed by the Arab World (Bayoumy et al, 2016;El Rassi et al, 2018). Kaba and Ramaiah (2019) used bibliometric techniques to highlight the productivity and impact of research on the internet of things (IoT) contributed by the Arab World. The researchers found better performance by the Arab World in IoT as compared to medical and environmental research.…”
Section: Literature Reviewmentioning
confidence: 99%